2014
DOI: 10.1016/j.fuproc.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

A CFD study of biomass pyrolysis in a downer reactor equipped with a novel gas–solid separator — I: Hydrodynamic performance

Abstract: This study presents the first part of a CFD study on the performance of a downer reactor for biomass pyrolysis. The reactor was equipped with a novel gas-solid separation method, developed by the co-authors from the ICFAR (Canada). The separator, which was designed to allow for fast separation of clean pyrolysis gas, consisted of a cone deflector and a gas exit pipe installed inside the downer reactor.A multi-fluid model (Eulerian-Eulerian) with constitutive relations adopted from the kinetic theory of granula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 19 publications
4
59
0
Order By: Relevance
“…To provide a robust tool for the development, optimization and scale up analysis domain can be found in part I of this study [7]. This is described briefly here as a column of 6.9 cm diameter and 133.5 cm height connected at the lower part to a solid receiving tank.…”
Section: IVmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide a robust tool for the development, optimization and scale up analysis domain can be found in part I of this study [7]. This is described briefly here as a column of 6.9 cm diameter and 133.5 cm height connected at the lower part to a solid receiving tank.…”
Section: IVmentioning
confidence: 99%
“…In the first part of this study, Yu et al [7] theoretically studied a downer reactor equipped with a novel solid gas separation mechanism. The study presented a valid computational fluid dynamic (CFD) model to predict the reactor multiphase flow features and provide the platform for further development to predict biomass pyrolysis behaviour and products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid-gas separation method applied in this study is relatively new and its application in chemical reactors has only been reported in few recent studies by Huard et al 27 and Yu et al [28][29] . In these studies, it was shown that the separation device can achieve more than 99% separation efficiency in downer reactors.…”
Section: Hydrodynamics and Temperature Distributionmentioning
confidence: 99%
“…27,28 Figure 7. Temporal evolution of the solid separation efficiency measured at the tip of the gas exit pipe.…”
Section: Solid-gas Separation and Devolatilization Efficienciesmentioning
confidence: 99%